Integrated Named Entity Recognition and Identical-Entity Detection for Extracting Unique Information Sources in News Articles - Ansyah, Adi Surya Suwardi; Oranova Siahaan, Daniel; izqi Paradisiaca , Brian R (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2025)
Native advertising is often difficult to detect because it resembles regular news articles. One indicator is the absence of diverse information sources or the reliance on a single perspective. Therefore, it is necessary to employ an extraction technique capable of consolidating various forms of identical entity mentions. This study integrates an NER model based on XLNet+BiLSTM+CRF with identical entity classification using Levenshtein distance features and static and contextual vector representations. The results show an F1-score of 93.71% at the entity level and 92.84% for identical entity identification, along with a list of unique citation sources. These findings demonstrate that this unique list can be an additional feature in detecting native advertising, which often relies on a single source. With an average unique entity coverage of 97.40%, the proposed architecture can extract unique entities within news articles